2015
DOI: 10.18632/oncotarget.6530
|View full text |Cite
|
Sign up to set email alerts
|

IL-27 induces the expression of IDO and PD-L1 in human cancer cells

Abstract: IL-27 is a member of the IL-12 family that is produced by macrophages and dendritic cells. IL-27 inhibits the growth and invasiveness of different cancers and therefore represents a potential anti-tumor agent. By contrast, it may exert immune-regulatory properties in different biological systems. We reported that IL-27 induces the expression of the IL-18 inhibitor IL-18BP, in human Epithelial Ovarian Cancer (EOC) cells, thus potentially limiting the immune response. Here, we tested whether IL-27 may modulate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
120
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 123 publications
(127 citation statements)
references
References 69 publications
7
120
0
Order By: Relevance
“…It is known to play a critical role in regulating the interaction between innate and adaptive antitumor immunity and has been shown to possess the ability to inhibit tumor growth and invasiveness [36]. There is increasing interest in cancer immunotherapy and modulation of the patients’ immune system to target cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…It is known to play a critical role in regulating the interaction between innate and adaptive antitumor immunity and has been shown to possess the ability to inhibit tumor growth and invasiveness [36]. There is increasing interest in cancer immunotherapy and modulation of the patients’ immune system to target cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…Perhaps more importantly, it induced the expression of the immune-suppressive molecules IDO and PD-L1, in human cancer cells, through the activation of STAT1 or STAT3 pathways, respectively [23]. It is noteworthy that both IL-27 and IFN-γ induce IL-18BP, PD-L1, and IDO, suggesting that these cytokines may have other, yet unknown, common effects.…”
Section: Introductionmentioning
confidence: 99%
“…21 In ovarian cancer cells, PD-L1 expression was reported to be up-regulated by IL-27 and IFN-γ via activation of Stat1 and Stat3. 22 However, there have been few studies related to PD-L1/2 expression in aggressive lymphomas. In the present study, we demonstrated that PD-L1/2 expression was significantly reduced by a Stat3 inhibitor, and this finding might be the first report to show a relationship between PD-L1/2 expression and Stat3 in lymphoma.…”
Section: Discussionmentioning
confidence: 99%